Factors influencing prehospital delay time among patients with peripheral arterial occlusive disease. (1st June 2016) - Vasaroangrong, Tidarat; Thosingha, Orapan; Riegel, Barbara; Ruangsetakit, Chanean; Viwatwongkasem, Chukiat
Abstract: Background: Only one-third of patients with peripheral arterial occlusive disease (PAOD) seek medical care after perceiving the symptoms of PAOD, and most PAOD patients only visit the physician when they develop ulceration and gangrene. Delay can result in lower extremity amputation and death within three years. The aim of this study was to predict prehospital delay time from sociodemographic characteristics and clinical characteristics, social support, knowledge about PAOD, depression and fear, and treatment-seeking behaviors among patients with PAOD. Method and results: Data were collected in three university hospitals in Bangkok, Thailand. A sample of 212 patients with PAOD who were newly diagnosed or diagnosed within the preceding four months was recruited into the study. Questionnaires and interviewing were used to collect data. Stepwise multiple regression analysis was performed to identify the factors influencing prehospital delay time. Significant determinants of prolonged prehospital delay time were male gender, low monthly income (less than 10, 000 Thai baht or 213 Euros), high level of perceived social support, and several treatment seeking behaviors. Depression, high level of fear, and self-pay of medical expenses were associated with short prehospital delay time. Overall, the model explained 41.0% of the variance in prehospital delay time. Conclusion: Clinicians need to develop intervention programs and national campaigns to increase knowledge about PAOD among patients in these high risk groups.